Light and electron microscopic studies on the interrenal tissue of the adrenal gland in Japanese quail (Coturnix coturnix japonica) - BASHA, SABIHA H; VIJAYARAGAVAN, C; RAMESH, GEETHA (The Indian Journal of Animal Sciences, 2014)
The interrenal tissue ofthe adrcnal gland was studicd in different age groups of Japanese quail viz juvenile. immature, mature and senile birds. The interrenal tissue or the adrenal cortex was distinguished into a peripheral zone and a central inner zone. The interrenal cells were columnar and differentiated into types 1,2, 3 and 4 cells. The interrenal cells of the subcapsular zone were arranged in the form of loops and were made of type 1 cells. The cells of the central zone were stacked in double row and consisted of type 2 cells, The type 3 cells were distributed in the intermediatc layer between subcapsular zone and the central zone. Type 4 cells werc rarely found in the subcapsular zone. Ultrathin sections of the tissue showed that these interrenal cells were rich in mitochondria, smooth endoplasmic reticulum and lipid droplets. Atrophic changes in the intcrrenal tissue was observed in molting phase and hyperplasIa of the interrenal cells was recorded in senile birds.